2010
DOI: 10.1073/pnas.0912896107
|View full text |Cite
|
Sign up to set email alerts
|

Design of embedded chimeric peptide nucleic acids that efficiently enter and accurately reactivate gene expression in vivo

Abstract: Pharmacological treatments designed to reactivate fetal γ-globin can lead to an effective and successful clinical outcome in patients with hemoglobinopathies. However, new approaches remain highly desired because such treatments are not equally effective for all patients, and toxicity issues remain. We have taken a systematic approach to develop an embedded chimeric peptide nucleic acid (PNA) that effectively enters the cell and the nucleus, binds to its target site at the human fetal γ-globin promoter, and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…2a), followed by differentiation of HSCs into erythroid progenitors (29). Consistent with data suggesting that Ppm1b is a negative regulator of Cdk9, whose activity is required for globin expression during both zebrafish and human erythropoiesis (36), we observed an increase in ␤-globin RNA concomitant with a decrease in Ppm1b protein levels (Fig.…”
Section: Eklf Physicallysupporting
confidence: 77%
See 1 more Smart Citation
“…2a), followed by differentiation of HSCs into erythroid progenitors (29). Consistent with data suggesting that Ppm1b is a negative regulator of Cdk9, whose activity is required for globin expression during both zebrafish and human erythropoiesis (36), we observed an increase in ␤-globin RNA concomitant with a decrease in Ppm1b protein levels (Fig.…”
Section: Eklf Physicallysupporting
confidence: 77%
“…After 7 days of expansion, 1.5 ϫ 10 6 cells per sample were nucleofected with 200 nM siPpm1b (supplemental Table S3) or untargeted siRNA (Qiagen) using the Amaxa Human CD34 ϩ nucleofection kit (program U-008) (28). Erythroid differentiation was induced with Epo (4 units/ml) and SCF (100 ng/ml) (29) in SFEM media 24 h after nucleofection. Cells were collected 72 h after differentiation for analysis by RT-PCR.…”
Section: Methodsmentioning
confidence: 99%
“…Our hypothesis is consistent with data recently published in the literature [9] and is supported by the results of fluorescence experiments; other assays, as for example the Chromatin Association Assay might be carried out to demonstrate that PNA S bind to DNA in vivo . [52] Data obtained so far underline how critical is the efficiency in the uptake to determine the biological activity of PNA analogues. In conclusion PNA S is the first example reported so far of antigene γ PNA bearing a negative charge.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that show direct and specific targeting of iNOS mRNA both in vitro and in vivo are limited. Our work and that of others have shown that peptide nucleic acid (PNA) has a number of useful properties that make it an ideal choice for targeting candidate mRNA [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…PNA, a synthetic analogue of DNA [20], is an ideal platform for the development of antisense diagnostic agents owing to its high resistance to enzymatic degradation, high affinity for RNA, ability to invade regions of secondary structure and inability to activate RNase H, which would otherwise degrade the target mRNA sequence and lead to signal loss [13,15,16,[21][22][23]. Although PNAs have been used in many biological applications as biosensors and imaging agents [14,18], poor membrane permeability and rapid clearance have limited its in vitro and in vivo applications [22,24].…”
Section: Introductionmentioning
confidence: 99%